PENERAPAN MODEL KOOPERATIF TIPE TEAM ACCELERATED INTRUCTION (TAI) UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN TEMATIK - Muhammad Kosasih, Aden (STKIP Subang, 2017)
This study aims to improve students' activity and learning outcomes by using Cooperative Learning model of Team Accelerated Intruction (TAI) type on the theme of the togetherness of my nation's cultural diversity subtema. This research is conducted in class IV SDN Komplek Karang Taruna Sari and background of student condition which show less activity in group process and result of learning which still many criteria of minimal mastery because teacher often use lecture motto which tend monoton and not yet use model Cooperative Learning Type Team Accelerated Intruction (TAI) consists of 8 phases: pretest, brief material, heterogeneous small group, group work group, presentation of group work, posttest, best group setting, and formative test. Assessment used in this research is pretest and posttest test technique to know student learning result, activeness assessment and observation sheet to know teacher and student attitudes during learning process. The results showed an increase in the average of the assessment of liveliness and learning test results. On the assessment of the activity of the average value of cycle 1 is 57.73 while cycle 2 reaches 67.31 and 3 cycles reaches 82.01 Learning outcomes in cycle 1 average score of 65.66, in cycle 2 reaches 70.16 and Learning outcomes in cycle 3 reached 76.33. This shows that the use of Cooperative Learning Model Type Team Accelerated Intruction (TAI) can improve the activity and learning outcomes of students on the theme of togetherness subtema cultural diversity of my nation class IV SDN Komplek Karang Taruna Sari. Thus, the use of Cooperative Learning model of Team Accelerated Intruction (TAI) type can be used as a learning model to be applied to thematic learning with other themes and subthemes.